Global cognitive dysfunction and β-amyloid neuropathology in late-life and treatment-resistant major depression. Issue 16 (26th December 2022) - Li, Cheng-Ta; Fuh, Jong-Ling; Yang, Bang-Hung; Hong, Chen-Ji; Chang, Chi-Wei; Tu, Pei-Chi; Jeng, Jia-Shyun; Chen, Mu-Hong; Tsai, Shih-Jen; Bai, Ya-Mei; Su, Tung-Ping; Lee, Hsuan; et al.
Abstract: Background: Cognitive impairment is common in late-life depression, which may increase Alzheimer disease (AD) risk. Therefore, we aimed to investigate whether late-life major depressive disorder (MDD) has worse cognition and increases the characteristic AD neuropathology. Furthermore, we carried out a comparison between treatment-resistant depression (TRD) and non-TRD. We hypothesized that patients with late-life depression and TRD may have increased β -amyloid (A β ) deposits in brain regions responsible for global cognition. Methods: We recruited 81 subjects, including 54 MDD patients (27 TRD and 27 non-TRD) and 27 matched healthy controls (HCs). Neurocognitive tasks were examined, including Mini-Mental State Examination and Montreal Cognitive Assessment to detect global cognitive functions. PET with Pittsburgh compound-B and fluorodeoxyglucose were used to capture brain A β pathology and glucose use, respectively, in some patients. Results: MDD patients performed worse in Montreal Cognitive Assessment ( p = 0.003) and had more A β deposits than HCs across the brain (family-wise error-corrected p < 0.001), with the most significant finding in the left middle frontal gyrus. Significant negative correlations between global cognition and prefrontal A β deposits existed in MDD patients, whereas positive correlations were noted in HCs. TRD patients had significantly more deposits in the left-sided brain regions (corrected p < 0.001). The findings were not explained by APOE genotypes. No between-group fluorodeoxyglucose difference was detected. Conclusions: Late-life depression, particularly TRD, had increased brain A β deposits and showed vulnerability to A β deposits. A detrimental role of A β deposits in global cognition in patients with late-onset or non-late-onset MDD supported the theory that late-life MDD could be a risk factor for AD.